Arthrocentesis Versus Pharmacological Therapy for the Management of Patients with Temporomandibular Joint Disc Displacement Disorders: TMJ Disc Displacement: Arthrocentesis vs. Pharmacotherapy - Ayyaz, Aneeza; Aqib Sohail; Fareed ud Din Ahmad Chishti; Ayesha Muhammad Rana; Zoya Aslam; Ali Ammar Hasan (Journal of University College of Medicine and Dentistry, 2025)
Objective: To compare the effectiveness of arthrocentesis versus pharmacological therapy in improving maximal mouth opening (MMO) in patients with temporomandibular joint (TMJ) disc displacement disorders. Methods: This clinical experimental study was conducted at the Department of Oral and Maxillofacial Surgery, Lahore Medical and Dental College, from June 20 to December 20, 2024. Patients aged 16 to 65 years with TMJ disc displacement, characterized by pain (VAS >3) and restricted mouth opening (<20 mm) for more than one month, were included after providing written informed consent. Exclusion criteria were hypersensitivity to pregabalin, prior TMJ surgery, connective tissue or metabolic disorders (e.g., diabetes, hypertension), and pregnancy. Sixty patients were randomly assigned to two groups: Group A received pregabalin 75 mg twice daily for four weeks, while Group B underwent arthrocentesis. MMO was recorded at baseline and after one month. Results: Among 60 enrolled patients, 30 were male and 30 female. Most participants (78.3%) were aged 21–40 years, and 68.3% had symptoms for less than 12 months. No significant differences in baseline demographics were observed between groups (p > 0.05). The mean improvement in MMO was significantly higher in the arthrocentesis group (8.98 mm) than in the pregabalin group (5.25 mm) (p < 0.001). The improvement was particularly significant among younger patients, both genders, and those with symptom duration under 12 months (p < 0.001). Conclusion: Arthrocentesis resulted in significantly greater improvement in maximal mouth opening compared to pregabalin, especially in younger patients and those with recent-onset TMJ disorders.